2005
DOI: 10.1097/01.bpo.0000153876.82442.1a
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Pattern of Femoral Shortening Following Devascularization of the Capital Femoral Epiphysis in Piglets

Abstract: To investigate the developmental pattern of femoral shortening in Legg-Calve-Perthes disease, the authors made an experimental model of the disease in piglets by devascularizing the capital femoral epiphysis and following the piglets to skeletal maturity. The discrepancy first increased in the postoperative 0 to 8 weeks (1.2-1.9 mm of shortening per week), then decelerated for a considerable period during the postoperative 8 to 16 weeks (0.2-0.6 mm per week), and then increased again toward the end of the grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
0
7
0
4
Order By: Relevance
“…By 20 weeks, there is severe deformity including marked collapse of the femoral head and acetabular dysplasia. This group also demonstrated that there were growth disturbances associated with an increase in femoral shortening over the 20-week time period [21]. Using growing minipigs, Schulitz et al [22] ligated all of the veins draining the femoral head.…”
Section: Animal Models Of Perthes Diseasementioning
confidence: 95%
“…By 20 weeks, there is severe deformity including marked collapse of the femoral head and acetabular dysplasia. This group also demonstrated that there were growth disturbances associated with an increase in femoral shortening over the 20-week time period [21]. Using growing minipigs, Schulitz et al [22] ligated all of the veins draining the femoral head.…”
Section: Animal Models Of Perthes Diseasementioning
confidence: 95%
“…Também, propõem-se introduzir os testes de avaliação da marcha para análise funcional. [11][12][13][14][15][16][17][18] deformidade da CF é mais evidente a partir deste período de isquemia. 11 Operaram-se onze leitões, híbridos comerciais (cruzamento das raças Large White e Landrace), machos, pesando entre 4 e 6 kg, idade de 3 a 4 semanas.…”
Section: Introductionunclassified
“…One concern, however, was that it further shortened the affected leg and thus increased the need for the epiphyseal arrest of the normal opposite leg 9, [20][21][22] . It is generally accepted that the amount of the shortening of the affected legs in LCPD depends almost exclusively on the severity of inhibition of endochondral ossification in the proximal femoral growth plate.…”
Section: DI Is Sc Cu Us Ss Si Io On Nmentioning
confidence: 99%
“…However, the disadvantages of FVO are also reported that it may shorten the limb and may create excessive varus angulation, leading to weakness of the abductors of the hip 19,21,24) . However, only few papers have been reported the long term results of FVO which followed up to the full skeletal maturity.…”
Section: In Nt Tr Ro Od Du Uc Ct Ti Io On Nmentioning
confidence: 99%
See 1 more Smart Citation